PENGARUH TIKTOK EDUKASI TERHADAP PENGETAHUAN DAN SIKAP VULVA HYGIENE SAAT MENSTRUASI DI SMP N 2 MELAYA - Sunantri, Ni Putu Ayu Nira; Sanjiwani, Ida Arimurti; Pramitaresthi, I Gusti Ayu; Astuti, Ika Widi (Coping: Community of Publishing in Nursing; Vol 12 No 3 (2024): Juni 2024DO - 10.24843/coping.2024.v12.i03.p03, 2024)
Menstruation is the release of the uterine layer (endometrium) that occurs every month marked by bleeding. During menstruation it is important to maintain the health and hygiene of the reproductive organs by performing vulva hygiene . Lack of knowledge in performing vulva hygiene  can lead to the emergence of various diseases in the reproductive organs. This research aims to find out the influence of TikTok education on knowledge and attitudes related to vulva hygiene  during menstruation in SMP N 2 Melaya. The research used pre-experimental design with one-group pre-test and post-test design. The sample involved in this study was 40 students selected by stratified random sampling. The test results on the knowledge variable with the Wilcoxon Signed Rank Test showed a p value = 0,001 (<0,05) and on the attitude variables with the Paired Sample T Test shows a p worth = 0,001(<0,05). It can be concluded that there is an influence of TikTok on the knowledge and attitude related to vulva hygiene  during menstruation in SMP N 2 Melaya. Implications to this study are that TikTok can be used as a method of giving education in improving knowledge and attitudes related to vulva hygiene  during menstruation in SMP N 2 Melaya.